Peningkatan Efisiensi Termal Tungku Biomasa Untuk Proses Pengeringan Biji Kakao di Desa Wiyono Kabupaten Pesawaran Propinsi Lampung - Muhammad Badaruddin; Ahmad Yudi Eka Risano; Ahmad Suudi (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2017)
Abstract — The modification stove was designed and constructed for drying cocoa beans using biomassa as fuel. The purpose of the modification stove is to increase production of 0.6 tonnes dry cocoa beans. The thermal efficiency of the stove is determined and compared with a conventional stove using hevea brasiliensis woods as fuel. The inside wall of stove and oven were built from SK34 fire brick and ceramic paper, respectively. The outer walls were made from red brick and was coated by cement. The results show that the thermal efficiency of the modification stove is increased by 37.34% compared with the conventional stove. The fuel consumption decreases by 25 % (25 kg-product), resulting a fuel cost saving of Rp. 1.8 million/year. In addition, the total cost of the stove can be paid back in a period of 3.5 years with the service lifetime of the stove for 10 years. The moisture contents ratio of cocoa beans with drying time are obtained to predict values of diffusivity (De) over range of drying temperature 50-80 °C. the values of diffusivity obtained ranged from 62.03 × 10−10 sampai 4.55 × 10−10 m2/s for the temperature used. Keywords — biomass stove, cocoa been, thermal efficiency, efective diffusity